Heterogeneity of G6PD deficiency prevalence in Mozambique: a school-based cross-sectional survey in three different regions. (December 2017) - Galatas, Beatriz; Mabote, Lurdes; Simone, Wilson; Matambisso, Gloria; Nhamussua, Lidia; Mañú-Pereira, María; Menéndez, Clara; Saute, Francisco; Macete, Eusebio; Bassat, Quique; Alonso, Pedro; Aide, Pedro
Abstract Background Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an X-linked hereditary enzymatic abnormality that affects more than 400 million people worldwide. Most deficient individuals do not manifest any symptoms; however, several precipitant agents—such as fava intake, infections, or several drugs—may trigger acute haemolytic anaemia. Countries should be informed of the prevalence of this enzymatic anomaly within their borders, in order to make safe and appropriate national decisions regarding the use of potentially unsafe drugs for G6PD deficient individuals. Methods A school-based cross-sectional survey was conducted in three districts in Mozambique, namely Manhiça, located in the south; Mocuba in the centre; and Pemba in the northern tip of the country. G6PD deficiency was evaluated using the CareStart™ diagnostic test, and enzyme activity levels were measured through fluorescence spectrophotometry in deficient individuals. Chi squared and ANOVA tests were used to assess prevalence and mean enzyme activity differences, and logistic regression was used to identify risk factors associated to the deficiency. Results G6PD deficiency prevalence estimates were lowest in the northern city of Pemba (8.3%) and among Emakhuwas and Shimakondes, and higher in the centre and southern regions of the country (16.8 and 14.6%, respectively), particularly among Elomwes and Xichanganas. G6PD deficiency was significantly more prevalent among male students than females (OR = 1.4, 95% CI 1.0–1.8, p = 0.02), although enzyme activity levels were not different among deficient individuals from either gender group. Finally, median deficiency levels were found to be more severe among the deficient students from the north (0.7 U/gHg [0.2–0.7] p < 0.001) and south (0.7 U/gHg [0.5–2.5]), compared to those from the centre (1.4 U/gHg [0.6–2.1]). Conclusion These findings suggest that Mozambique, as a historically high malaria-endemic country has considerable levels of G6PD deficiency, that vary significantly across the country. This should be considered when planning national strategies for the use of licensed drugs that may be associated to haemolysis among G6PD individuals, or prior to the performance of future trials using primaquine and other 8-aminoquinolines derivatives. Registration Number CISM local ethics committee (CIBS-25/013, 4th of December 2013), and the National Ethics Committee of Mozambique (IRB00002657, 28th of February 2014).